Analisis Perbandingan Model Pendeteksi Financial Distress Pada Perusahaan Sektor Aneka Industri: - - Tesa Rahmita; Ferdawati Ferdawati; Reni Endang Sulastri (Politeknik Caltex Riau, 2023)
This research aims to determine the financial condition of various industrial sector companies listed on the Indonesia Stock Exchange for the period 2015-2019, using a purposive sampling method with a total sample of 13 companies. The type of data used is secondary data obtained from the company's financial statements. This study uses 3 models of financial distress analysis, namely the Springate, Grover and CA-Score models. The results of this study indicate that the Springate model predicts that twelve companies are in a state of distress for five consecutive years and one company is in a state that changes from distress to non-distress. The Grover model predicts that four companies are in a state of distress, four companies are in a non-distress condition and five companies are in a fluctuating condition for five consecutive years. The CA-Score model predicts that there are five companies that are in a distress condition, five companies are in a non-distress condition and three companies that are in a fluctuating condition for five consecutive years.